Advances in Red Palm Oil as Functional Food Ingredient: Composition, Stability, and Applications in Food Systems - Jaluwardhana, Rivan Satria; Cahyana, Yana; Mulyono, Asep; Arifin, Heni Radiani; Marta, Herlina; Nurjayati, Ratih; Melanie, Hakiki; Khayrani, Apriliana Cahya (Fakultas Teknologi Industri Pertanian, 2026)
Indonesia, as one of the world’s leading producers of palm oil, plays a strategic role and has significant potential to develop palm oil–derived products, such as red palm oil (RPO), as future functional food ingredients. The growing demand for nutritious and sustainable foods has spurred exploration of natural resources with enhanced functional and technological value. This comprehensive review summarizes recent advances in the utilization of red palm oil (RPO) as a functional food ingredient, with particular emphasis on its composition, bioactive compounds, physicochemical stability, and processing versatility The literature search was conducted using a Narrative Literature Review (NLR) approach to identify relevant publications from 2000 to 2024 across major scientific databases. Priority was given to studies published within the last ten years to capture recent developments, while earlier publications were included as foundational and theoretical references that remain relevant to the field. RPO is rich in β-carotene, tocopherols, and tocotrienols, which contribute to its antioxidant activity, distinctive red–orange colour, and oxidative stability. These characteristics support the incorporation of RPO into a wide range of food formulations, including bakery products, spreads, and emulsion-based systems. This review integrates current evidence on the role of RPO in sustainable food diversification, provides insights into its technological applications, and highlights future research opportunities to optimize its utilization in modern food innovation.